Pedagogical practices with social impact in the Computer Science School of the National University of La Plata : interdisciplinary articulation for the development of a digital communicator for autistic children - Queiruga, Claudia Alejandra; Harari, Ivana; Rosso, Jorge Horacio (2015)
The involvement of public universities in the solution of problems in society and the participation in the processes of social and production development of the country are goals of university education in Argentina. The use of ICTs as instruments that contribute to Independence, quality of life and inclusion of persons with disabilities is a topic of concern for many disciplines worldwide. This paper presents HERMES, a project involving the articulation of two subjects of the Computer Science School of the National University of La Plata – "Diseño Centrado en el Usuario" ("User-Centered Design") and "Laboratorio de Software" ("Software Laboratory") and the civil organization CEDICA, a referent in the province of Buenos Aires regarding the application of AAT (Animal- Assisted Activities) among people with disabilities (physical, cognitive, sensory, psychological and social). HERMES consists on the development of a digital communicator based on pictograms, available for tablets, aimed at children and teenagers with an Autism Spectrum Disorder (ASD) attending CEDICA. This project involves students and teachers of both subjects and CEDICA professionals, families, and children and teenagers with an ASD, in the process of design and development of the communicator. Currently, the first prototype of HERMES is under evaluation. We conclude that this type of initiatives tend to complement the academic training of students, promoting an open and integrating culture within the computer science community, accepting diversity in all contexts and contributing to the solution of the problems in its community.
Formato de archivo PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
Congreso Argentino de Ciencias de la Computación (21ro : 2015 : Junín, Argentina)
Keywords: JAVA; ANDROID; APLICACIONES MÓVILES; autismo